PENGEMBANGAN PERANGKAT PEMBELAJARAN PENEMUAN TERBIMBING UNTUK MELATIH KEMAMPUAN BERPIKIR KRITIS SISWA - Denok Julianingsih (Yayasan Akrab Pekanbaru, 2018)
This study aims to produce a learning tool guided discovery learning valid, practical, and effective way to train the students 'critical thinking skills in statistical material in class VII SMP and describe the effectiveness of guided discovery learning in training students' critical thinking skills in statistical material. This study uses a model of development of Kemp continued with the implementation phase of learning in the classroom using a design one group pretest-posttest design. The research was conducted in two classes, namely class as a class test 7A and 7B class as implementation class. Data from pilot studies in the class is mastery learning outcomes of students in classical by 77.14% and positive student responses for each component of the questionnaire given to the students the percentage is â‰¥60% chose the category yes. While research data on the implementation class is the teacher able to manage learning activities well, that is the value of the overall average for the three meetings is 4.39. Positive student response that is more than 70% of students responded yes to every aspect assessed on questionnaire responses. Completed student learning outcomes in the amount of 77,78% whose value is â‰¥70, it means that there are 8 student whose value is below the established criteria. Students' critical thinking skills, which amounted to 63.88% of the students in the class VII B have good critical thinking skills with medium and high categories. Keywords: Guided Discovery Learning, Critical Thinking Skills, Complete learn. Abstrak